VALUES SUPPORTING THE SUSTAINABILITY OF INCLUSIVE EDUCATION IN DIFFERENT PRACTICES - Galkiene, Alvyra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article analyses how fundamental values underpin educational practices that have emerged in the development of society and create the preconditions for the sustainability of inclusive education. Through the analysis of the scholarly literature, the expression of inclusive values in the application of approaches to integrated, individualised inclusive education and Universal Design for Learning is analysed. It has been established that the effectiveness of inclusive education is substantiated in practices which are based on real existing inclusive values: equity, equality, communality and respect for diversity. Based on the results of the study, it is concluded that the sustainability of inclusive education coincides with the real existence of inclusive values in practice, equally applying to all students.